Media Pembelajaran Global Warming - Fikri Jufri Tham; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2016)
Computer based learning media is one of the media has an important role in learning. Learning media will be attractive when packaged through interactive media , such as interactive media created in paper manufacture